Tinjauan Literatur Teori Kognitif dan Konstruktivisme dalam Pembelajaran - Habsy, Bakhrudin All; Fitriano, Lino; Sabrina, Nailah Aura; Mustika, Ayunda Laras (TSAQOFAH, 2024)
This research aims to analyze cognitive and constructivism theory in learning based on a literature review of 10 journals including national and international journals. This research uses a qualitative method with a literature study type of research. The stages of conducting the research started from conducting a literature review from 10 journals regarding cognitive and constructivism theory in learning then analyzing the research starting from data collection, reduction, data display, to drawing conclusions. The results of this study indicate that both collaborative and engaged learning have a positive impact on peer and instructor interactions; both factors influence online learning during the COVID-19 pandemic, increasing student happiness and academic success. The use of social media as a forum for educational learning, student collaboration and participation, as well as the use of social media as a forum for online interaction and learning during the COVID-19 pandemic are in the spotlight.